Coating preparation method of spinel coating on surface of stainless steel connector for fuel cell

The spinel coating is prepared by using acrylate binder and reduction-oxidation sintering step-by-step treatment process on the stainless steel connector, which solves the problem of oxidation of metal connectors at high SOFC temperatures, improves the density and bonding strength of the coating, and extends the service life of the battery.

CN119608552AInactive Publication Date: 2025-03-14NORTH CHINA ELECTRIC POWER UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510051231.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, metal connectors are easily oxidized at high SOFC temperatures, resulting in reduced conductivity and cracking of oxide films, which affects battery performance and life. In particular, the thickness and volatility of the Cr2O3 layer lead to cathode toxicity and affects battery commercialization.

Method used

The step-by-step treatment process of acrylate adhesive, coating and reduction-oxidation sintering is adopted, and the three points are combined to uniformly control the coating thickness, increase the coating density and mechanical properties, and improve the interface bonding strength between spinel coating and stainless steel connectors.

Benefits of technology

Through this method, the density and mechanical properties of the spinel coating are significantly improved, the bonding strength between the coating and the stainless steel connector is enhanced, the coating is prevented from falling off and cracking, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608552A_ABST
    Figure CN119608552A_ABST
Patent Text Reader

Abstract

The invention provides a coating preparation method of a spinel coating on the surface of a stainless steel connector for a fuel cell. The coating preparation method comprises the following steps: carrying out surface pretreatment on the stainless steel connector; nanoscale manganese-cobalt spinel powder, an acrylate binder and water are mixed to prepare coating slurry, the surface of the stainless steel connector subjected to surface pretreatment is coated with the coating slurry at the normal temperature according to the preset wet coating thickness, airing treatment, reduction treatment and oxidation sintering treatment are sequentially conducted, and a spinel coating is obtained; the reduction atmosphere is mixed gas of hydrogen and inert gas, the oxidation atmosphere is air, the reduction temperature and the oxidation temperature are both 800-900 DEG C, the reduction time is 2-5 h, and the oxidation time is 2-10 h. According to the method, the nanoscale powder, the acrylate binder, the coating and the reduction-oxidation sintering step-by-step treatment process are combined in a three-point mode, the thickness of the coating is evenly controlled, the compactness and mechanical performance of the coating are improved, and the interface bonding strength of the spinel coating-stainless steel connector is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of connector coating preparation, and in particular to a coating preparation method for a spinel coating on the surface of a stainless steel connector for a fuel cell. Background Art

[0002] Solid oxide cell (SOC) is a green and clean energy conversion device that can operate in two modes: fuel cell and electrolytic cell, realizing efficient conversion, storage and re-conversion of renewable electricity. Since SOFC single cell has low output power and low voltage, it needs to be assembled into a battery stack through connectors in series or parallel. The main function of the connector is to electrically connect adjacent cells and separate the gases on the cathode and anode sides. Metal connectors are widely used in solid oxide fuel cells because of their low cost, conductivity and convenient machining. However, when SOFC works at high temperature, metal connectors are easily oxidized. After Cr in the metal connector is oxidized, Cr2O3 with low conductivity is generated on the metal surface. This oxide film can prevent further oxidation of the metal. However, due to structural defects, oxygen passes through the oxide film and causes internal metal oxidation. At the same time, internal metal ions are also easily diffused out of the oxide layer and oxidized. The oxygen penetration and metal ion diffusion process at high temperature are further aggravated. As the Cr2O3 layer thickens, the resistance continues to increase, which makes the conductivity of the connector decrease, and even the oxide film cracks and peels off, losing the protection of the metal, further accelerating the oxidation of the metal and causing the connector to deform, which seriously affects the performance of the battery. Under the cathode atmosphere, the oxide film on the surface of the metal connector will volatilize into gaseous oxides and diffuse to the electrode interface, causing the electrode activity to decrease and affecting the battery performance. The volatilized Cr will cause cathode poisoning. The Cr-containing gaseous substances in the Cr-based alloy connector will volatilize and deposit on the cathode surface, causing the cathode performance to decay rapidly. Solving the problem of Cr-poisoned cathode is one of the technical difficulties that need to be overcome to achieve the commercialization of SOFC. In the field of material surface treatment technology, alloy connectors are a common material, and their surface properties directly affect the performance and service life of the product. However, during the use of alloy connectors, due to their insufficient surface properties, such as corrosion resistance, wear resistance, and oxidation resistance, surface treatment is often required to improve their performance. Among them, coating preparation technology is a commonly used surface treatment method. By preparing a coating with specific properties on the surface of the alloy connector, the surface properties of the alloy connector can be effectively improved, thereby improving its service life and performance.

[0003] Spinel coating is widely used in metal connector protective coating due to its good anti-oxidation and electrical conductivity. Manganese cobalt spinel is a material that can exist stably at high temperatures and is a connector coating material with excellent comprehensive coefficients.

[0004] The commonly used preparation methods of spinel coatings, such as slurry method, hot coating method and sol-gel method, have problems of poor density and bonding performance, and require high-temperature sintering, or first reduction to metal and then oxidation conversion to spinel layer.

[0005] The spinel coating is prepared by electroplating, chemical plating, sputtering and other methods. It needs thermal conversion to form the spinel layer. The density and bonding performance of the coating are excellent. However, the stainless steel connector coating is prone to cracking and falling off during the long-term operation of SOC, which reduces the performance and life of the battery stack. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell, which combines an acrylic ester binder, coating and reduction-oxidation sintering step-by-step treatment process to uniformly control the coating thickness, increase the coating density and mechanical properties, and improve the interface bonding strength between the spinel coating and the stainless steel connector.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows: A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell, comprising the following steps:

[0008] Perform surface pretreatment on stainless steel connectors;

[0009] The coating slurry is prepared by mixing manganese cobalt spinel powder, a binder and water; preferably, the mixing is carried out by ball milling, the ball milling speed is 90 r / min to 200 r / min, and the ball milling time is 24 h to 48 h;

[0010] The coating slurry is coated on the surface of the stainless steel connector after surface pretreatment at a temperature of 20°C to 25°C with a preset wet coating thickness, and then dried, reduced and oxidized and sintered in sequence to obtain a spinel coating; preferably, the coating is performed using a coater at a coating speed of 2mm / s to 10mm / s;

[0011] During the reduction treatment, the reduction atmosphere is a mixture of hydrogen and inert gas, the reduction temperature is 800° C. to 900° C., and the reduction time is 2 h to 5 h;

[0012] During the oxidation sintering treatment, the oxidation atmosphere is air, the oxidation temperature is 800° C. to 900° C., and the oxidation time is 2 h to 10 h.

[0013] The reduction-oxidation sintering step-by-step treatment process can burn off the organic phase in the reduction process to obtain the metal phase, and then the oxidation sintering treatment makes the crystal particles grow and the mass expand, thereby increasing the bonding strength of the spinel coating / stainless steel connector interface and the bonding strength between the Mn-Co spinel particles, and the coating is not easy to fall off and crack.

[0014] Preferably, the chemical formula of the manganese cobalt spinel powder raw material is Mn x Co 3-x O4, where 0 < x < 3. Further, the manganese cobalt spinel powder is a commercial spinel powder, which can reduce the actual firing temperature of the coating (below 1000°C), and this actual firing temperature is much lower than the sintering temperature of the coating (1200°C), which can solve problems such as low density and poor mechanical properties of the finally obtained spinel coating.

[0015] Preferably, the manganese cobalt spinel powder is a nano-level powder.

[0016] Preferably, the binder is acrylate. The acrylate binder has excellent adhesion on the surfaces of metals and metal oxides, which is beneficial to achieving a strong interface bond between the spinel coating and the stainless steel connector, enhancing the adhesion between the coating / substrate and the cohesion between the particles within the coating.

[0017] Preferably, the preset wet coating thickness is 75 μm to 150 μm.

[0018] Preferably, the inert gas includes nitrogen.

[0019] Preferably, in the reducing atmosphere: the flow rate of hydrogen is 6 sccm to 20 sccm, the mass content of hydrogen is 3% to 10%, the flow rate of nitrogen is 80 sccm to 94 sccm, and the mass content of nitrogen is 40% to 47%.

[0020] Preferably, the material of the stainless steel connector is ferritic stainless steel. Further, the ferritic stainless steel is ferritic stainless steel including SUS 430, SUS 441, Crofer 22APU, Crofer 22H.

[0021] Preferably, the steps of the surface pretreatment include:

[0022] Grind the surface of the stainless steel connector;

[0023] Degrease the surface of the ground stainless steel connector with isopropyl alcohol;

[0024] Ultrasonically clean the surface of the degreased stainless steel connector with absolute ethanol;

[0025] Dry the surface of the ultrasonically cleaned stainless steel connector.

[0026] Preferably, the mass ratio of the manganese cobalt spinel powder, the binder and water is 1:1:5 to 1:1:10. When the solid content of the coating slurry is higher than 1:1:5, the slurry is too thick, which will cause the coating to accumulate; when the solid content of the coating slurry is lower than 1:1:10, the slurry is too thin, which will cause the coating to break.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention combines the three steps of acrylic ester adhesive, coating and reduction-oxidation sintering to uniformly control the coating thickness, increase the coating density and mechanical properties, and improve the interface bonding strength of the spinel coating-stainless steel connector.

[0029] The present invention adopts a room temperature coating method, which has low preparation cost, simple operation, and can control the coating thickness to be uniform; adopts a reduction-oxidation sintering step-by-step treatment process, and can burn out the organic phase in the reduction process to obtain the metal phase, and then perform oxidation sintering treatment to make the crystal particles grow and expand the mass, thereby increasing the bonding strength of the spinel coating / stainless steel connector interface and the bonding strength between the Mn-Co spinel particles, and the coating is not easy to fall off and crack.

[0030] The spinel coating prepared by the present invention can improve the problems that the stainless steel connector coating is prone to cracking and falling off during the long-term operation of SOC, thereby reducing the performance and life of the battery stack. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Mn prepared in Example 1 of the present invention 1.5 Co 1.5 SEM surface morphology spectrum of O4 spinel coating;

[0032] Figure 2 Mn prepared in Example 1 of the present invention 1.5 Co 1.5 SEM cross-sectional morphology spectrum of O4 spinel coating;

[0033] Figure 3 Mn prepared in Example 1 of the present invention 1.5 Co 1.5 O4 spinel coating oxidation weight gain test curve;

[0034] Figure 4 Mn obtained in comparative example 2 of the present invention 1.5 Co 1.5 SEM cross-sectional morphology spectrum of O4 spinel coating;

[0035] Figure 5 Mn obtained in comparative example 3 of the present invention 1.5 Co 1.5 SEM cross-sectional morphology spectrum of O4 spinel coating. DETAILED DESCRIPTION

[0036] It is worth noting that the methods used in the present invention are all conventional methods unless otherwise specified; the raw materials and devices used are all conventional commercially available products, and their sources are not specifically limited unless otherwise specified.

[0037] A coating preparation method for a spinel coating on the surface of a stainless steel connector for a fuel cell, comprising the following steps:

[0038] Perform surface pretreatment on the stainless steel connector; preferably, the steps of surface pretreatment include:

[0039] Grind the surface of the stainless steel connector; preferably, the sandpaper used for grinding is preferably 800 mesh to 1000 mesh; the thickness of the stainless steel connector is preferably 1.5 mm to 3 mm, and the size of the stainless steel connector is preferably 20 mm × 20 mm;

[0040] Degrease the surface of the ground stainless steel connector with isopropyl alcohol; preferably, the degreasing treatment is carried out in ultrasonic, and the time for degreasing treatment in ultrasonic is preferably 10 min to 15 min;

[0041] Ultrasonically clean the surface of the degreased stainless steel connector with absolute ethanol, and the ultrasonic cleaning time is preferably 10 min to 15 min;

[0042] Dry the surface of the ultrasonically cleaned stainless steel connector, and it can be directly air-dried.

[0043] Mix manganese cobalt spinel powder, binder and water to prepare a coating slurry; preferably, the mass ratio of manganese cobalt spinel powder, binder and water is 1:1:5 to 1:1:10, more preferably, the mass ratio of manganese cobalt spinel powder, binder and water is 7:7:50

[0044] Preferably, the chemical formula of the manganese cobalt spinel powder raw material is Mn x Co 3-x O4, 0 < x < 3, more preferably, the manganese cobalt spinel powder is Mn 1.5 Co 1.5 O4 spinel powder, and the manganese cobalt spinel powder is a nano-level powder; the binder is selected as acrylate, which can enhance the mechanical properties of the coating and the bonding force between the substrate and the surface coating, and the water is selected as ultrapure water;

[0045] In some preferred embodiments, the mixing is carried out by ball milling, the ball milling speed is 90 r / min to 200 r / min, preferably 90 r / min, and the ball milling time is 24 h to 48 h; more preferably, first mix the manganese cobalt spinel powder and water and ball mill for 24 h, then add the binder and ball mill for another 24 h to finally obtain the coating slurry;

[0046] The coating slurry is slowly and evenly dripped into the coater at a temperature of 20°C to 25°C (no bubbles are allowed), the coater is pulled at a uniform speed to maintain a coating speed of 2mm / s to 10mm / s (too fast or too slow will result in uneven coating), and the surface of the stainless steel connector after surface pretreatment is coated with a preset wet coating thickness, and then dried, reduced and oxidized and sintered in sequence to obtain a spinel coating; the coating and coating method has low cost, simple operation, and can control the coating thickness to be uniform; reduction and oxidation sintering step by step after coating can increase the density of the spinel coating, preferably, the preset wet coating thickness is 75μm to 150μm, more preferably 150μm; preferably, the thickness of the spinel coating is 5μm to 40μm, more preferably the thickness of the spinel coating is 10μm;

[0047] Preferably, the coating is carried out using a coater at a coating speed of 2 mm / s to 10 mm / s, more preferably, the coating speed is 3 mm / s to 5 mm / s;

[0048] During the reduction treatment: the reducing atmosphere is a mixture of hydrogen and an inert gas, preferably, the inert gas includes nitrogen; the reducing temperature is 800° C. to 900° C., and the reducing time is 2 h to 5 h, preferably, the reducing temperature is 800° C. to 850° C., and the reducing time is 2 h to 3 h;

[0049] During the oxidation sintering treatment, the oxidation atmosphere is air, that is, ambient air is selected as the oxidation atmosphere, the oxidation temperature is 800°C to 900°C, and the oxidation time is 2h to 10h. Preferably, the oxidation temperature is 850°C to 900°C, and the oxidation time is 2h to 5h.

[0050] Preferably, during the reduction treatment or the oxidation sintering treatment, the heating rate is preferably 2°C / min to 3°C / min, and the cooling rate is preferably furnace cooling.

[0051] In some preferred embodiments, in the reducing atmosphere: the purity of hydrogen and nitrogen is respectively greater than 99%, the flow rate of hydrogen is 6sccm~20sccm, preferably, the flow rate of hydrogen is 6sccm~10sccm, the mass content of hydrogen is 3%~10%, preferably, the mass content of hydrogen is 3%~5%, the flow rate of nitrogen is 80sccm~94sccm, preferably, the flow rate of nitrogen is 90sccm~94sccm, the mass content of nitrogen is 40%~47%, preferably, the mass content of nitrogen is 45%~47%.

[0052] Preferably, the stainless steel connector is made of ferritic stainless steel. Further, the ferritic stainless steel includes SUS 430, SUS 441, Crofer 22APU, and Crofer 22H.

[0053] Example 1

[0054] A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell comprises the following steps:

[0055] Step 1: Take a 1.5mm thick Crofer 22H ferritic stainless steel plate and cut it into a 20mm*20mm stainless steel connector (sample). Grind the surface of the stainless steel connector with 1000-grit sandpaper, then ultrasonically clean and degrease it in isopropanol, then ultrasonically clean it in anhydrous ethanol, and then dry it for later use.

[0056] Step 2: Add Mn 1.5 Co 1.5 O4 spinel powder and ultrapure water were mixed evenly at a mass ratio of 7:50, 5mm ball milling beads were added to the above raw materials and then ball milled at a speed of 90r / min for 24h. Acrylic binder was added to the raw materials after ball milling, Mn 1.5 Co 1.5 The mass ratio of O4 spinel powder, acrylate binder and ultrapure water is 7:7:50. The mixed raw materials are ball-milled again at a ball-milling speed of 90 r / min and a ball-milling time of 24 h to finally obtain a coating slurry.

[0057] Step 3: Apply the coating slurry in step 2 to the stainless steel connector pretreated in step 1 at room temperature, with a coating speed of 5 mm / s. The wet coating thickness is controlled to be about 150 μm by the coater. After coating, dry naturally at room temperature for 12 hours for use.

[0058] Step 4: Place the coated stainless steel connector in a tubular furnace with a reducing atmosphere for reduction heat treatment (the reducing atmosphere is a mixture of H2 and N2), heat up to 800°C at a rate of 2°C / min, keep warm for 2 hours, and cool with the furnace. The purity of H2 and N2 used in the reduction process is greater than 99%, the volume content of H2 is 3%, and the flow rate of H2 is 6sccm.

[0059] Step 5: Place the reduced coated stainless steel connector in a tubular furnace with an oxidizing atmosphere for oxidation heat treatment (the oxidizing atmosphere is ambient air), heat up to 800°C at a rate of 2°C / min, keep warm for 2h, and cool with the furnace. 1.5 Co 1.5 O4 spinel coating. 1.5 Co 1.5 The surface morphology and cross-sectional morphology of O4 spinel coatings are shown in Figure 1 , 2 ,from Figure 1 Visible Mn 1.5 Co 1.5The particles on the surface of the O4 coating are closely and evenly distributed, the particles are firmly bonded, and the density of the coating is significantly improved. Figure 2 It can be seen that a continuous and uniform Mn layer with a thickness of about 8 μm (7.871 μm for H1 and 8.653 μm for H2) is formed on the surface of the stainless steel connector. 1.5 Co 1.5 O4 spinel coating, and the coating is tightly connected to the surface of the stainless steel connector;

[0060] The surface preparation of Mn in Example 1 1.5 Co 1.5 Oxidation weight gain test of Crofer 22H ferritic stainless steel connector with O4 spinel coating, see Figure 3 In the figure, Crofer-coating 1 and Crofer-coating 2 are both materials prepared in Example 1, 430-coating 1 means that the remaining steps are the same as those in Example 1, and only the material of the stainless steel connector in Example 1 is replaced with 430 stainless steel, uncoated 430 means an uncoated 430 stainless steel connector, uncoated Crofer means an uncoated Crofer22H ferritic stainless steel connector, and pre-uncoated Crofer means a Crofer22 H ferritic stainless steel connector with a pre-coating (conventional protective coating). It can be found that compared with the uncoated stainless steel connector, the weight of the Crofer 22H stainless steel connector prepared in Example 1 does not increase significantly under long-term air exposure, and its weight hardly changes significantly over time. The weight of other stainless steel connectors increases to varying degrees under long-term air exposure.

[0061] Example 2

[0062] A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell comprises the following steps:

[0063] Step 1: Take a 1.5mm thick Crofer 22H ferritic stainless steel plate and cut it into a 20mm*20mm stainless steel connector (sample). Grind the surface of the stainless steel connector with 800-grit sandpaper, then ultrasonically clean and degrease it in isopropanol, then ultrasonically clean it in anhydrous ethanol, and then dry it for later use.

[0064] Step 2: Add Mn 1.5 Co 1.5 O4 spinel powder and ultrapure water were mixed evenly at a mass ratio of 10:50, 5mm ball milling beads were added to the above raw materials and then ball milled at a speed of 90r / min for 24h. Acrylic binder was added to the raw materials after ball milling, Mn 1.5 Co 1.5The mass ratio of O4 spinel powder, acrylate binder and ultrapure water is 10:10:50. The mixed raw materials are ball-milled again at a ball-milling speed of 90 r / min and a ball-milling time of 24 h to finally obtain a coating slurry.

[0065] Step 3: Apply the coating slurry in step 2 to the stainless steel connector pretreated in step 1 at room temperature, with a coating speed of 5 mm / s, a coating pressure of 0.3 MPa, and a coating distance of 20 cm. The wet coating thickness is controlled by controlling the number of coatings, and the wet coating thickness is about 20 μm. After coating, dry naturally at room temperature for 12 hours for use.

[0066] Step 4: Place the coated stainless steel connector in a tubular furnace with a reducing atmosphere for reduction heat treatment (the reducing atmosphere is a mixture of H2 and N2), heat up to 800°C at a rate of 2°C / min, keep warm for 2 hours, and cool with the furnace. The purity of H2 and N2 used in the reduction process is greater than 99%, the volume content of H2 is 3%, and the flow rate of H2 is 6sccm.

[0067] Step 5: Place the reduced coated stainless steel connector in a tubular furnace with an oxidizing atmosphere for oxidation heat treatment (the oxidizing atmosphere is ambient air), heat up to 800°C at a rate of 2°C / min, keep warm for 2h, and cool with the furnace. 1.5 Co 1.5 O4 spinel coating.

[0068] Example 3

[0069] A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell comprises the following steps:

[0070] Step 1: Take a 1.5mm thick SUS 430 ferrite stainless steel plate and cut it into a 20mm*20mm stainless steel connector (sample). Grind the surface of the stainless steel connector with 1500-grit sandpaper, then ultrasonically clean and degrease it in isopropyl alcohol, then ultrasonically clean it in anhydrous ethanol, and then dry it for later use.

[0071] Step 2: Add Mn 1.5 Co 1.5 O4 spinel powder and ultrapure water were mixed evenly at a mass ratio of 10:40, 5mm ball milling beads were added to the above raw materials and then ball milled at a speed of 90r / min for 24h. Acrylic binder was added to the raw materials after ball milling, Mn 1.5 Co 1.5 The mass ratio of O4 spinel powder, acrylate binder and ultrapure water is 10:10:40. The mixed raw materials are ball-milled again at a ball-milling speed of 90 r / min and a ball-milling time of 24 h to finally obtain a coating slurry.

[0072] Step 3: Apply the coating slurry in step 2 to the stainless steel connector pretreated in step 1 at room temperature, with a coating speed of 5 mm / s. The coating pressure is 0.3 MPa and the coating distance is 20 cm. The wet coating thickness is controlled by controlling the number of coatings, and the wet coating thickness is about 20 μm. After coating, the coating is naturally dried at room temperature for 12 hours for use. However, due to the high solid content of the slurry and the excessive thickness of the slurry, the coating is accumulated locally and the coating is uneven.

[0073] Step 4: Place the coated stainless steel connector in a tubular furnace with a reducing atmosphere for reduction heat treatment (the reducing atmosphere is a mixture of H2 and N2), and heat up to 850°C at a rate of 2°C / min, keep warm for 2 hours, and cool with the furnace. The purity of H2 and N2 used in the reduction process is greater than 99%, the volume content of H2 is 4%, and the flow rate of H2 is 8sccm.

[0074] Step 5: Place the reduced coated stainless steel connector in a tubular furnace with an oxidizing atmosphere for oxidation heat treatment (the oxidizing atmosphere is ambient air), raise the temperature to 850°C at a heating rate of 2°C / min, keep it for 3 hours, and cool it with the furnace. The spinel coating on the stainless steel connector is obtained, and it is found that although the coating is dense, the coating thickness is uneven due to the excessive thickness of the slurry.

[0075] Comparative Example 1

[0076] A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell comprises the following steps:

[0077] Step 1: Take a 1.5mm thick SUS 441 ferrite stainless steel plate and cut it into a 20mm*20mm stainless steel connector (sample). Grind the surface of the stainless steel connector with 1000-grit sandpaper, then ultrasonically clean and degrease it in isopropyl alcohol, then ultrasonically clean it in anhydrous ethanol, and then dry it for later use.

[0078] Step 2: Add Mn 1.5 Co 1.5 O4 spinel powder and ultrapure water were mixed evenly at a mass ratio of 10:110, 5mm ball milling beads were added to the above raw materials and then ball milled at a speed of 90r / min for 24h. Acrylic binder was added to the raw materials after ball milling, Mn 1.5 Co 1.5 The mass ratio of O4 spinel powder, acrylate binder and ultrapure water is 10:10:110. The mixed raw materials are ball-milled again at a ball-milling speed of 90 r / min and a ball-milling time of 24 h to finally obtain a coating slurry.

[0079] Step 3: Apply the coating slurry in step 2 to the stainless steel connector pretreated in step 1 at room temperature, with a coating speed of 5 mm / s, a coating pressure of 0.2 MPa, and a coating distance of 20 cm. The wet coating thickness is controlled by controlling the number of coatings, and the wet coating thickness is about 20 μm. After coating, the coating is naturally dried at room temperature for 12 hours for use. It was found that the coating was intermittent and partially broken due to the low solid content and thin slurry.

[0080] Step 4: Place the coated stainless steel connector in a tubular furnace with a reducing atmosphere for reduction heat treatment (the reducing atmosphere is a mixture of H2 and N2), heat up to 800°C at a rate of 2°C / min, keep warm for 2 hours, and cool with the furnace. The purity of H2 and N2 used in the reduction process is greater than 99%, the volume content of H2 is 3%, and the flow rate of H2 is 6sccm.

[0081] Step 5: Place the reduced coated stainless steel connector in a tubular furnace with an oxidizing atmosphere for oxidation heat treatment (the oxidizing atmosphere is ambient air), heat up to 800°C at a rate of 2°C / min, keep warm for 2h, and cool with the furnace. 1.5 Co 1.5 O4 spinel coating, but the coating broke due to the thin slurry and the coating was partially not dense.

[0082] Comparative Example 2

[0083] A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell comprises the following steps:

[0084] Step 1: Take a 1.5mm thick Crofer 22APU ferritic stainless steel plate and cut it into a 20mm*20mm stainless steel connector (sample). Grind the surface of the stainless steel connector with 2000-grit sandpaper, then ultrasonically clean and degrease it in isopropanol, then ultrasonically clean it in anhydrous ethanol, and then dry it for later use.

[0085] Step 2: Add Mn 1.5 Co 1.5 O4 spinel powder and ultrapure water were mixed evenly at a mass ratio of 10:50, 5mm ball milling beads were added to the above raw materials and then ball milled at a speed of 90r / min for 24h. Acrylic binder was added to the raw materials after ball milling, Mn 1.5 Co 1.5 The mass ratio of O4 spinel powder, acrylate binder and ultrapure water is 10:10:50. The mixed raw materials are ball-milled again at a ball-milling speed of 90 r / min and a ball-milling time of 24 h to finally obtain a coating slurry.

[0086] Step 3: Spray the coating slurry in step 2 onto the stainless steel connector pretreated in step 1 at room temperature with a spray pressure of 0.1 MPa and a spray distance of 10 cm. It was found that the spray gun could not spray a continuous and uniform coating, see Figure 4 , and then sprayed with a coating slurry of 1:1:10. The spray gun still could not spray continuously. Replacing the nano-scale powder with micron-scale powder and spraying with the same proportion of slurry was normal. Therefore, nano-scale powder cannot produce a uniform and dense coating by spraying.

[0087] Comparative Example 3

[0088] A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell comprises the following steps:

[0089] Step 1: Take a 1.5mm thick Crofer 22APU ferritic stainless steel plate and cut it into a 20mm*20mm stainless steel connector (sample). Grind the surface of the stainless steel connector with 2000-grit sandpaper, then ultrasonically clean and degrease it in isopropanol, then ultrasonically clean it in anhydrous ethanol, and then dry it for later use.

[0090] Step 2: Add Mn 1.5 Co 1.5 O4 spinel powder and ultrapure water were mixed evenly at a mass ratio of 10:50, 5mm ball milling beads were added to the above raw materials and then ball milled at a speed of 90r / min for 24h. Acrylic binder was added to the raw materials after ball milling, Mn 1.5 Co 1.5 The mass ratio of O4 spinel powder, acrylate binder and ultrapure water is 10:10:50. The mixed raw materials are ball-milled again at a ball-milling speed of 90 r / min and a ball-milling time of 24 h to finally obtain a coating slurry.

[0091] Step 3: At room temperature, the coating slurry in step 2 is plated onto the stainless steel connector pretreated in step 1 by a pulling and dipping method, with a pulling speed of 1 cm / s. It was found that it was not possible to pull out a continuous and uniform coating by dipping, see Figure 5 , and then dip and pull with a coating slurry of 1:1:10, but the coating still could not be continuously held.

[0092] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for coating and preparing a spinel coating on the surface of a stainless steel connector for a fuel cell, characterized in that: The following steps are involved: Perform surface pretreatment on stainless steel connectors; The coating slurry is prepared by mixing nano-sized manganese cobalt spinel powder, an acrylate binder and water; The coating slurry is applied to the surface of the stainless steel connector after surface pretreatment at a temperature of 20° C. to 25° C. with a preset wet coating thickness, and then drying, reducing and oxidizing and sintering are performed in sequence to obtain a spinel coating; During the reduction treatment, the reduction atmosphere is a mixture of hydrogen and inert gas, the reduction temperature is 800° C. to 900° C., and the reduction time is 2 h to 5 h; During the oxidation sintering treatment, the oxidation atmosphere is air, the oxidation temperature is 800° C. to 900° C., and the oxidation time is 2 h to 10 h.

2. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1, characterized in that: The chemical formula of the manganese-cobalt spinel powder raw material is Mn x Co 3-x O4,0 <x<3。 3. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1 or 2, characterized in that: The manganese-cobalt spinel powder is a nanometer-scale powder.

4. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1, characterized in that: The adhesive is acrylate.

5. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1, characterized in that: The preset wet coating thickness is 75 μm to 150 μm.

6. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1, characterized in that: The inert gas includes nitrogen.

7. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 6, characterized in that: In the reducing atmosphere, the flow rate of hydrogen is 6 sccm to 20 sccm, the mass content of hydrogen is 3% to 10%, the flow rate of nitrogen is 80 sccm to 94 sccm, and the mass content of nitrogen is 40% to 47%.

8. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1, characterized in that: The stainless steel connector is made of ferritic stainless steel.

9. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1, characterized in that: The surface pretreatment step comprises: Grinding the surface of the stainless steel connector; Use isopropyl alcohol to degrease the polished surface of the stainless steel connector; The surface of the stainless steel connector after degreasing is ultrasonically cleaned with anhydrous ethanol; The surface of the stainless steel connector after ultrasonic cleaning is dried.

10. The method for coating and preparing the spinel coating on the surface of a stainless steel interconnector for a fuel cell according to claim 1, characterized in that: The mass ratio of the manganese-cobalt spinel powder, the binder and water is 1:1:5 to 1:1:10.

Citation Information

Patent Citations

  • Alloy high temperature oxidation resisting nanostructure conductive coating prepared with spinel powder reduction method

    CN101671829A

  • Solid oxide battery connector protective coating and preparation method thereof

    CN117374312A

  • Fuel cell, stainless steel connector and spraying preparation method of MnCo2O4 spinel coating on surface of stainless steel connector

    CN118547274A

  • Post-heat treatment method of spinel powder for plasma spray coating on metallic interconnects for solid oxide fuel cells

    KR101969873B1